PENGARUH CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS (Studi Empiris pada Perusahaan Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022) - Fiolina, Allisa; Yuyetta, Etna Nur Afri (Diponegoro Journal of Accounting, 2024)
This research was conducted to examine the effect of corporate governance on financial distress. Variables used in the examination are managerial ownership, institutional ownership, foreign ownership, board of commissioner, independence commissioner, and board of directors as the dependent variables, and also financial distress as the dependent variable.The samples of this study are transportation and logistics companies listed on the Indonesia Stock Exchange from 2020 - 2022. The samples based on the purposive sampling method obtained a sample of 28 companies with a total of 84 samples for 3 years of research. The data is processed using logistic regression analysis.The results showed that foreign ownership, the board of commissioners, independence commissioners, and the board of directors did not affect the financial distress. While other findings indicate that other variables, managerial ownership and institutional ownership, have a negative and significant impact on financial distress.